Ekranisasi dan Nilai Religius Novel Wedding Agreement Karya Mia Chuz - Noor Tsalis Yuni Kusumawati; Apsanti Djokosujanto; Bambang Sumadyo (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2020)
The purpose of this research is to show the ecranization and religious values used in Mia Chuz's Wedding Agreement novel.. This research is in the form of a qualitative descriptive with a content analysis method based on the objects obtained from the ecranization and religious values contained in the Wedding Agreement novel by Mia Chuz. The results of this study indicate that there are 118 ekranization processes that occur in the elements of the plot, character, and setting, namely the existence of shrinkage, addition, and variation change. The shrinking of the plot, characters, and settings occurs because the media used in making novels and films are different. The addition of the plot, characters, and settings in the film as a whole is still relevant to the story in the novel, it's just that the visualization in the film is made more interesting, while for the varied changes in plot, character, and setting made in the visualization to the form of the film as a whole it is not far from being depicted in the